Rates of Stent Thrombosis in Bare-Metal Versus Drug-Eluting Stents (from a Large Australian Multicenter Registry) - Yan, B.; Duffy, S.; Clark, D.; Lefkovits, J.; Warren, R.; Gurvitch, R.; Lew, R.; Sebastian, M.; Brennan, A.; Andrianopoulos, N.; Reid, Christopher; Ajani, A. (Excerpta Medica, Inc, 2008)
Recent reports suggest that drug-eluting stents (DESs) may increase the risk of stent thrombosis (ST) relative to bare-metal stents (BMSs). Therefore, the aim of this study was to compare DES and BMS outcomes with a specific focus on ST. We analyzed 30-day and 1-year outcomes of 2,919 patients who underwent percutaneous coronary intervention with stent implantation from the Melbourne Interventional Group registry. Academic Research Consortium definitions of ST were used: (1) definite ST (confirmed using angiography in patients with an acute coronary syndrome), (2) probable ST (unexplained death <30 days or target-vessel myocardial infarction without angiographic confirmation), and (3) possible ST (unexplained death >30 days). Multivariate analysis was performed to identify predictors of ST. The incidence of ST (early or late) was similar between BMSs and DESs (1.6% vs 1.4%; p = 0.66), and DES use was not predictive of ST. Independent predictors of ST included the absence of clopidogrel therapy at 30 days (odds ratio [OR] 2.58, 95% confidence interval [CI] 1.29 to 5.29, p <0.01), renal failure (OR 3.30, 95% CI 1.43 to 7.59, p <0.01), index procedure presentation with an acute coronary syndrome (OR 2.59, 95% CI 1.14 to 5.87, p = 0.02), diabetes mellitus (OR 2.25, 95% CI 1.19 to 4.23, p = 0.01), and total stent length =20 mm (OR 1.85, 95% CI 1.00 to 3.42, p = 0.04). In conclusion, DESs were not associated with increased risk of ST compared with BMSs at 12 months in this large Australian registry that selectively used DESs for patients at high risk of restenosis. © 2008 Elsevier Inc. All rights reserved.